Parametric analysis of the effect of operation parameters on asphaltene deposition: An experimental study. (18th October 2017) - Bemani, Amin; Ashoori, Siavash; Bahrami, Masoud
ABSTRACT: Changing pressure, temperature, and composition cause instability in crude oil and create a problematic issue which is called asphaltene deposition. Asphaltene deposition causes problems in wettability alteration and flow assurance in different parts of petroleum industry so asphaltene deposition becomes a challenging issue in petroleum engineering. Hence, it is necessary to predict asphaltene deposition and investigate parameters which effect on asphaltene deposition. In this contribution, because of similarity between pore throat of reservoir rock and capillary tube, to investigate parameters such as asphaltene content, precipitant ratio, flow rate, and temperature effect on asphaltene deposition, a capillary setup was constructed and a model was developed to relate pressure drop along capillary tube to permeability reduction.